The Effect of Structure Building Small Mammals in a Shifting Arctic Landscape - Austin Roy; Jennie R. McLaren (Ecology and Evolution, 2025)
ABSTRACT Landscapes are undergoing ecological changes, and how organisms interact with changing habitats has implications for zoogeochemical influences on ecosystem function (processes and properties). This may be especially true for organisms that alter nutrient cycling, such as structure builders, in nutrient‐limited systems such as the Arctic. Our aims were to examine the impact of brown lemming (Lemmus trimucronatus) structures (winter nests, runways, latrines, and burrows) on above‐ and below‐ground processes in habitats that represent contemporary (flat‐centered polygon) and potential future (high‐centered polygon) tundra conditions near Utqiaġvik, Alaska. Above‐ground, structures influenced vegetation community structure at local scales, with winter nests having lower moss and forb cover and burrows, latrines, and runways having lower litter and higher bare ground cover; although effects did not vary by habitat type. Furthermore, structures influenced plant diversity, which may be driven by structure types supporting unique plant species. Below‐ground, burrows had broad effects on soil nutrients, with soils under burrows generally having lower carbon and nitrogen contents and exo‐enzyme activities in both habitat types. Other structures increased nutrient availability, with soils under winter nests having higher ammonium concentrations compared to controls in both habitat types, whereas soils under latrines had higher phosphate and extractable organic carbon than controls, but only in high‐centered polygon tundra. Additionally, soil temperatures under winter nests were lower than at control sites, but only in flat‐centered polygon tundra, and soil pH was higher under winter nests and runways in both habitat types. Effects of structures on soil physical properties probably helped to regulate the effects of structures on soil nutrient availability. Finally, differences in structure effects between habitat types suggest that as high‐centered polygonal tundra becomes more prevalent, this herbivore's influence on ecosystem processes at local scales may feedback to alter the function of future arctic ecosystems.